RELIGIUSITAS SISWA BERAGAMA BUDDHA PADA SEKOLAH MENENGAH PERTAMA TAMAN RAMA DENPASAR - Rozi, Moh (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies); Volume 01, Nomor 01, Desember 2012, 2013)
To view the young people’s religiosity or adolescent in these Buddhists students at SMP Taman Rama Denpasar always leaned closer to their life with the their religion’s teachings, it can be seen in the habits of these children, so the children can be classified as children who are religious or not religious. One people mentioned religious if in the life concordant of the middle way, it’s the Buddha teaching. The middle way is the way to protect from life style to follow desire and to torture of itself. In the lifedays young people or adolescent lived not concordant with the Buddha teaching. In this case visible many negative behavior from the young people in the city, such as Denpasar city. Such as using motor without filter exile to result in noise sound. Many young people or adolescent incluiding in these buddhist student at SMP Taman Rama influenced by consumerisme lifestile, such as using Black Berry Hand phone this time model. This study was formulated in three issues, first, how does the implementation of Buddhist students’ religiosity at SMP Taman Rama Denpasar, second, what are the factors that affect the implementation of the Buddhist students’ religiosity at SMP Taman Rama Junior Denpasar, third, what is the meaning of the religious implementation Buddhist students’ religiosity SMP Taman Rama Denpasar. This study uses qualitative methods to the design of data collection techniques through observation, interview and literature study. The data collected were analyzed using descriptive qualitative and interpretive. In analyzing the data using the three theories, namely theory of practice, deconstruction theory and symbolic interactionisme theory. The third theory is used in elective to dissect the issues raised in this study. These results indicate that the first: Religiosity conducted by Buddhist students in SMP Taman Rama Denpasar in general there are similarities, such as by implementing the climbing chanting and meditation, perform puja in the dark (ceit) and the moon light (capgo), Atthangasila, Pancasila Buddhist and implement in daily life. Second: the Buddha teachings as a spur to the religion practice and the power of self-religiosity. Third: the meaning of Buddhist students’ religiosity SMP Taman Rama Denpasar include the meaning of solidarity, harmony, and inner meaning of peace.
Keywords: Religiosity, symbolic Interactionisme, practice, behavior